2010
DOI: 10.1097/scs.0b013e3181c36283
|View full text |Cite
|
Sign up to set email alerts
|

Composite Cartilage Island Grafts in Type 1 Tympanoplasty

Abstract: Tympanoplasty is a surgical procedure used for eradicating chronic middle ear infection and for reconstructing hearing in infected ears. Independent from the graft placing technique, the atrophy and the insufficiency of the graft material would be seen.For cases at high risk for failure, such as recurrent perforations, total perforations, and severely atelectatic tympanic membranes, many surgeons have used cartilage as a grafting material because of its increased stability and resistance to negative middle ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In studies regarding this issue, no statistically significant differences in hearing gains were found between cartilage graft and temporal muscle fascia graft patients (21-24). Karaman et al (22) reported that the rate of composite cartilage island graft closure of the tympanic membrane in 74 patients was 97.3% and that ABG improvement was 20.2 dB. Khan et al (23) reported a closing rate of 98.20% and an average improvement of 7.06 dB ABG in the study that they carried out using thinned tragal cartilage grafts.…”
Section: Discussionmentioning
confidence: 91%
“…In studies regarding this issue, no statistically significant differences in hearing gains were found between cartilage graft and temporal muscle fascia graft patients (21-24). Karaman et al (22) reported that the rate of composite cartilage island graft closure of the tympanic membrane in 74 patients was 97.3% and that ABG improvement was 20.2 dB. Khan et al (23) reported a closing rate of 98.20% and an average improvement of 7.06 dB ABG in the study that they carried out using thinned tragal cartilage grafts.…”
Section: Discussionmentioning
confidence: 91%
“…The greatest concern now is the thickness of the graft material that is used for reconstruction. Many studies documented the reduction in ABG closure and reduction in the compliance of the TM in the long run [15][16][17]. All these studies compare cartilage with fascia.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study is to evaluate the anatomical and audiological results using our technique for tympanic membrane pars tensa perforations in type I tympanoplasties. To our knowledge this is the first study describing results with sliced island tragal cartilage in type I tympanoplasty as studies reported previously use full thickness cartilage perichondrial grafts [3,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Karaman E and Duman C using full thickness composite cartilage island grafts in type I tympanoplasty, successful Graft take was achieved in 97.29% with mean postoperative pure-tone average air-bone gap improvement of 20.2 dB at 500 Hz, 23.58 dB at 1000 Hz, 22.23 dB at 2000 Hz, and 24.79 at 4000 Hz [5]. Whereas Kirazli T, Bilgen C et al with 15 patients, the mean postoperative gains in air-bone gap were 11.9 dB with the cartilage island [6].…”
mentioning
confidence: 99%